The effect of thyroid hormones on pregnant women who get abortion - Inas Sattar Abd; Yaqoub Yousif Ismai (Al-Qadisiyah Journal of Pure Science, 2018)
This study was performed during 2013 in Al-Batool hospital / Baquba, for fifty pregnant women. The ages were between (17-50) years who had been getting abortion as compared with (24) healthy women as control group (same age) . When the activity of thyroid hormones ( Triiodothyronine , Tetraiodothyronine - thyroxine and Thyroid stimulate hormone) were measured for both cases. Results showed that high rates of abortion had been occurred in the first trimester of pregnancy period while the low rates were in the second trimester of pregnancy period. The results also showed no significant relationship with respect to age among women who had undergone abortion, compared with control group. The study also showed that there was significant correlation between high rates Thyroid stimulate hormone with the number of women get abortion.